Glycogen Synthase Kinase-3 Beta Expression Correlates With Worse Overall Survival in Non-Small Cell Lung Cancer—A Clinicopathological Series - Alves, Marclesson; Borges, Daniela de Paula; Kimberly, Aline; Martins Neto, Francisco; Oliveira, Ana Claudia; Sousa, Juliana Cordeiro de; Nogueira, Cleto D.; Carneiro, Benedito A.; Tavora, Fabio (Frontiers in Oncology, 2021)
Background Glycogen Synthase Kinase-3 beta (GSK-3β) regulates diverse cell functions including metabolic activity, signaling and structural proteins. GSK-3β phosphorylates target pro-oncogenes and regulates programmed cell death-ligand 1 (PD-L1). This study investigated the correlation between GSK-3β expression and clinically relevant molecular features of lung adenocarcinoma (PDL1 score, PTEN expression and driver mutations). Methods We evaluated 95 lung cancer specimens from biopsies and surgical resections. Immunohistochemistry was performed to analyze the expression of GSK-3β, PTEN, and PDL1. Epidemiological data, molecular characteristics and staging were evaluated from medical records. The histologic classification was performed by an experienced pulmonary pathologist. Results Most patients were female (52.6%) and the majority had a positive smoking history. The median age was 68.3 years, with individuals over 60 years accounting for 82.1%. The predominant histological subtype was adenocarcinoma (69.5%), followed by squamous cell carcinoma (20.0%). GSK-3β expression in tumors was cytoplasmic with a dotted pattern and perinuclear concentration, with associated membranous staining. Seven (7.3%) tumors had associated nuclear expression localization. Seventy-seven patients (81.1%) had advanced clinical-stage tumors. GSK-3β was positive in 75 tumors (78%) and GSK3-positive tumors tended to be diagnosed at advanced stages. Among stage III/IV tumors, 84% showed GSK3 positivity (p= 0.007). We identified a statistically significant association between GSK-3β and PTEN in the qualitative analysis (p 0.021); and when comparing PTEN to GSK-3β intensity 2+ (p 0.001) or 3+ expression (> 50%) – p 0.013. GSK-3β positive tumors with a high histological score had a worse overall survival. Conclusion We identified the histological patterns of GSK-3β expression and evaluated its potential as marker for overall survival, establishing a simple histological score to measure the evaluated status in resected tissues. The use of GSK-3β expression as an immune response biomarker remains a challenge. Future studies will seek to explain the role of its interaction with PTEN.